Temporary Anchorage Devices usage stability in modern orthodontics: systematic review - Hryva, Liudmyla (The Ukrainian Scientific Medical Youth Journal, 2025)
In orthodontic treatment, TADs have mostly been utilized for anchorage when patient compliance is lacking. Various failure rates have been reported in modern orthodontic literature. An accurate assessment of the TADs stability rate and potential risk factors for the mechanically-retained TADs was the aim of our research. Up to December 2017, MEDLINE, Scopus, and the Cochrane Library were used for electronic database searches. Reference lists were examined and further searching for ongoing and unpublished data was done. Hand searches of pertinent journals and grey literature were also conducted. We gathered English-language published prospective cohort studies (PCSs) and randomised controlled trials (RCTs) that detailed the failure rate of miniscrews, which are less than 2 mm in diameter, when used as an orthodontic anchoring. In this study, data extraction, risk of bias evaluation, and blind and duplicate study selection were done. Using the random-effects model, failure rates and pertinent risk variables for miniscrews were determined, along with the accompanying 95 percent confidence intervals (CIs). The I2 and Chi2 tests were used to evaluate the heterogeneity among the studies. The Newcastle-Ottawa Scale and the Cochrane Risk of Bias were used to determine the risk of bias. The robustness of the meta-analysis results was tested by using subgroup and sensitivity analyses. This study comprised 30 prospective clinical trials as well as 16 randomized clinical trials. Because there was insufficient statistical data to calculate the impact sizes, five studies were excluded from the meta-analysis. In a random-effect model, 3250 miniscrews approximately amongst 41 trials were combined. Miniscrews showed an overall failure rate of 13.5% (95% CI 11.5%–15.9%). Analysis of division groups revealed that smoking and the kind of gingivae had statistically significant effects on the rate of miniscrew failure, while the diameter, length, and design of the miniscrews, patient age, and place of insertion had non-significant effects. Conclusion: TADs have an acceptably low failure rate. Because of the high degree of heterogeneity and imbalanced groups in the included research, care should be taken when interpreting the results. To validate the results of this review, significant sample sizes from high-quality randomized clinical trials are needed.